Cowboys, Ankle Sprains, and Keepers of Quality: How Is Video Game Development Different from Software Development? - Murphy-Hill, Emerson; Zimmermann, Tom; Nagappan, Nachi (Proceedings of the 36th International Conference on Software Engineering (ICSE 2014), 2014)
Video games make up an important part of the software industry, yet the software engineering community rarely studies video games. This imbalance is a problem if video game development differs from general software development, as some game experts suggest. In this paper we describe a study with 14 interviewees and 364 survey respondents. The study elicited substantial differences between video game development and other software development. For example, in game development, “cowboy coders” are necessary to cope with the continuous interplay between creative desires and technical constraints. Consequently, game developers are hesitant to use automated testing because of these tests’ rapid obsolescence in the face of shifting creative desires of game designers. These differences between game and non-game development have implications for research, industry, and practice. For instance, as a starting point for impacting game development, researchers could create testing tools that enable game developers to create tests that assert flexible behavior with little up-front investment.